Effects of Electroacupuncture at Different Points on Colorectal Distention-induced Changes in Blood Pressure, Electrogastrogram, Gastric Tension and Gastric Blood Flow - 陈淑萍 高永辉 王俊英 刘俊岭 (Journal of traditional Chinese medicine, 2011)
Objective： To investigate the specificity of the effects of electroacupuncture （EA） at different acupoints on gastric functional activity and gastric blood flow after colorectal distension （CRD） in the rat. Methods： Fifty Wistar rats were randomly divided into 5 groups： a control group, a Zusanli group, a non-point group, a Taichong group and a Neiguan group. Rats were anesthetized after 18 h of fasting, and a rat model of nociceptive blood pressure elevation and abnormal electrogastrogram （EGG） and gastric tension （GT） was prepared by gasbag-induced CRD. EA was given bilaterally, and its effects on gastric blood flow （GBF） of the arcus vasculosi of the greater omentum, blood pressure, EGG fast wave properties, and gastric smooth muscle tension （GT） were quantified. Results： CRD induced an increase in blood pressure that was significantly inhibited by EA at all points （all P〈0.05）, and the inhibitory effects were greater in the Zusanli and Neiguan groups compared to the non-point group （both P〈0.05）. CRD also caused reductions in GT and GBF, and in the amplitude, frequency and duration of EGG waves （all P〈0.05）. These effects were also reversed by EA. The effects of EA on EGG wave amplitude, GT, and GBF were superior in the Zusanli group compared to the Taichong group, Neiguan group, and the non-point group. Conclusion： EA significantly counteracted CRD-induced changes in blood pressure, GBF, EGG, and GT. The effects of stimulation at Zusanli （ST 36） were significantly greater compared to other points, indicating relative specificity of this acupoint.